Strategi Inovasi Desain Poduk Tas Fashion Kayu Mindi di Krebet Pajangan Bantul Yogyakarta - Moh. Rusnoto Susanto; Rahayu Retnaningsih; Kusuma Chandra Kirana (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
Currently, Yogjakarta as one of the target world tourism destinations certainly needs to prepare many things, especially in the industrial era 4.0 in the present. The first improvement is around human resources who have a strategic role in entering this era. The creative industry currently has sufficient opportunities to transfer technology, whether in waste processing (eg wood) as the basic material for creating functional products with global competitiveness. Especially in the Bantul area as an export-oriented handicraft production warehouse. In this research, we collaborated with UKM Partners 'Ruaya' which explored mindi wood as the main raw material for the creative industry. Ruaya is a home industry that focuses on making wood-based fashion bags. As for the activities carried out to achieve the output target agreed upon by the Partner, among others: First, conducting assistance activities for studio management and production management; Second, holding a design innovation workshop program to produce unique and highly competitive export superior products; Third, carry out a strengthening workshop program in the e-Commerce sector; Fourth, assisting the production process based on design innovation that was developed during the time with partners; Fifth, conducting a regulatory program and technical guidance on IPR registration by the IPR Extension Team from the Director General of IPR, and the Ministry of Human Rights, DIY, and Sixth, assisting in the process of drafting IPR drafts and registering IPRs.